KORELASI ANTARA CBR, PI DAN KUAT GESER TANAH LEMPUNG - Purnomo, Mego (Jurnal Teknik Sipil dan Perencanaan, 2011)
Abstract: In a practical planning sometimes does not need to do a soil test as a whole. Therefore requiresÃÂ  anÃÂ  approachÃÂ  fromÃÂ  theÃÂ  soilÃÂ  properties.ÃÂ  ToÃÂ  obtainÃÂ  anÃÂ  approachÃÂ  tersebutperluÃÂ  holdingÃÂ  of repeated experiments in the laboratory, so it can be described in a graphical form of the elationship between naturesifaatÃÂ  land. From garfikÃÂ  if one ofÃÂ  theÃÂ  factorsÃÂ  / characteristics are knownÃÂ  thenÃÂ  the other properties can be determined. This study used clay fromÃÂ  the site PucangÃÂ  Ivoire (Semarang), JalanÃÂ  PedurunganGenukÃÂ  (Semarang),ÃÂ  KarangawenÃÂ  (Demak),ÃÂ  HutÃÂ  (Purwodadi),ÃÂ  Godong (Purwodadi).ÃÂ  AndÃÂ  conductedÃÂ  researchÃÂ  inÃÂ  soilÃÂ  mechanicsÃÂ  laboratory.ÃÂ  FromÃÂ  theÃÂ  researchÃÂ  results obtained byÃÂ  theÃÂ  relationship between CBR and PIÃÂ  is PI = 137.866.792 CBR and PI = 90.796ÃÂ  to 4.574 CBR, CBR at an angle with the shear angle in the ground: ÃÂ¤ = 18.379 + 1.155 CBR and 1.71 ÃÂ¤ = 10.496 + CBR , CBR connection and cohesion, namely: CBR C = 0.165 0.279 and C = 0.174 CBR 0.5996, and PI relationship with the land gesr angle ÃÂ¤ = 49.9160.4 PI Keywords: Plastic Index, California Bearing Ratio, Strength Scroll, Clay Soil ÃÂ  Abstrak: Dalam suatu perencanaan praktis kadang tidak perlu melakukan percobaan tanah secara keseluruhan. Oleh karena itu membutuhkan suatu pendekatan dari sifat,sifat tanah tersebut. Untuk memperolehÃÂ  suatuÃÂ  pendekatanÃÂ  tersebutperluÃÂ  diadakannyaÃÂ  percobaanÃÂ  yangÃÂ  berulang,ulangÃÂ  di laboratorium, sehingga dapat digambarkan dalam suatu bentuk grafis hubungan antara sifat,sifaat tanah tersebut. Dari garfik tersebut jika salah satu faktor /sifat diketahui maka dapat ditentukan sifat yangÃÂ  lain.ÃÂ  PenelitianÃÂ  iniÃÂ  menggunakanÃÂ  tanahÃÂ  lempungÃÂ  dariÃÂ  lokasiÃÂ  PucangÃÂ  GadingÃÂ  (Semarang), JalanÃÂ  Pedurungan,GenukÃÂ  (Semarang),ÃÂ  KarangawenÃÂ  (Demak),ÃÂ  GubukÃÂ  (Purwodadi),ÃÂ  Godong (Purwodadi).ÃÂ  DanÃÂ  penelitianÃÂ  dilakukanÃÂ  diÃÂ  laboratoriumÃÂ  mekanikaÃÂ  tanah.ÃÂ  DariÃÂ  hasilÃÂ  penelitian diperolehÃÂ  hubunganÃÂ  antaraÃÂ  CBRÃÂ  danÃÂ  PIÃÂ  yaituÃÂ  PIÃÂ  =ÃÂ  137,86 ÃÂ Ã¢â¬âÃÂ  6,792CBRÃÂ  danÃÂ  PIÃÂ  =90,796ÃÂ  Ã¢â¬â 4,574CBR, CBR dengan sudut dengan sudut geserÃÂ  tanah dalam yaituÃÂ  : ÃÂ¤ = 18,379 + 1,155CBR dan ÃÂ¤=10,496 + 1,71CBR, hubunganÃÂ ÃÂ  CBR dan kohesi yaituÃÂ  : C = 0,165 CBR Ã¢â¬â 0,279 dan C = 0,174CBR Ã¢â¬â 0,5996, dan Hubungan PI dengan sudut gesr tanah dalam ÃÂ¤ = 49,916 Ã¢â¬â 0,4PI Kata kunci: Plastik Indek, California Bearing Ratio, Kuat Geser, Tanah Lempung